2023
DOI: 10.3390/ijms241310558
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Clinical, Molecular and Immunological Characterization of Pulmonary Sarcomatoid Carcinomas Reveals an Immune Escape Mechanism That May Influence Therapeutic Strategies

Abstract: Pulmonary sarcomatoid carcinoma (PSC) has highly aggressive biological behaviour and poor clinical outcomes, raising expectations for new therapeutic strategies. We characterized 179 PSC by immunohistochemistry, next-generation sequencing and in silico analysis using a deep learning algorithm with respect to clinical, immunological and molecular features. PSC was more common in men, older ages and smokers. Surgery was an independent factor (p < 0.01) of overall survival (OS). PD-L1 expression was detected i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 85 publications
0
6
0
Order By: Relevance
“…In contrast to these conventional cancer types, PSC, this exceptionally aggressive lung cancer subtype, exhibited high CD8 + T cell density, tumor‐associated macrophages, and PD‐L1 expression and was linked to poorer survival and a higher incidence of postoperative progression [ 50 ]. Over the past several years, targetable molecular alterations such as MET exon 14 skipping mutations were identified [ 1 , 4 , 6 , 51 , 52 , 53 , 54 , 55 , 56 ]. However, there were very few studies have assessed the comprehensive molecular landscape of PSC using multiomics approaches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to these conventional cancer types, PSC, this exceptionally aggressive lung cancer subtype, exhibited high CD8 + T cell density, tumor‐associated macrophages, and PD‐L1 expression and was linked to poorer survival and a higher incidence of postoperative progression [ 50 ]. Over the past several years, targetable molecular alterations such as MET exon 14 skipping mutations were identified [ 1 , 4 , 6 , 51 , 52 , 53 , 54 , 55 , 56 ]. However, there were very few studies have assessed the comprehensive molecular landscape of PSC using multiomics approaches.…”
Section: Discussionmentioning
confidence: 99%
“…However, there were very few studies have assessed the comprehensive molecular landscape of PSC using multiomics approaches. A recent study characterized 179 PSCs by immunohistochemistry, next‐generation sequencing, and in silico analysis with respect to clinical, immunological, and molecular features and revealed a high prevalence of MET exon 14 skipping mutations as well as high PD‐L1 expressions in PSCs [ 56 ]. In this study, we performed an integrative molecular analysis of 21 PSC samples using targeted gene sequencing, WES and RNA sequencing to comprehensively define the molecular underpinnings of this rare clinical entity.…”
Section: Discussionmentioning
confidence: 99%
“…In PSC patients, the incidence of ALK fusion mutations was 2.3% 43 and the incidence of ALK rearrangements was 3.5%. 44 In a case report, patients carrying ALK fusion-positive PSC, who had disease progression during treatment with pembrolizumab even though high PD-L1 expression was detected, experienced effective tumor remission after switching to targeted therapy with an ALK inhibitor.…”
Section: Immunotherapy For Psc With Driver Gene Mutationsmentioning
confidence: 99%
“…The significance of EGFR mutations in NSCLC has gained widespread recognition since they were first identified. The frequency of EGFR mutations in PSC is still controversial, with some studies suggesting that the frequency of EGFR mutations is as high as 20% in Asian populations ( 26 , 59 ), while it is lower in White populations ( 17 , 131 - 133 ). Types of EGFR mutations also vary across different studies.…”
Section: Clinical Characteristics and Treatmentmentioning
confidence: 99%
“…MET mutations are more prevalent in PSC compared to other types of NSCLC (~3%), especially MET exon 14 skipping mutations ( 38 , 133 , 141 , 142 ). It has been widely demonstrated that MET TKIs benefit patients with NSCLC and MET exon 14 skipping mutations (a multicenter retrospective analysis evaluating the efficacy of MET TKIs indicates that NSCLC patients receiving treatment have a longer mOS compared to those who did not, 25.3 vs. 10.9 months) ( 143 , 144 ).…”
Section: Clinical Characteristics and Treatmentmentioning
confidence: 99%